Harmful life style practices and associated factors among fishermen in Cuddalore district, Tamil Nadu: a cross sectional study - V., Prabhaharan; P., Kalyani; A., John William Felix (International Journal Of Community Medicine And Public Health, 2022)
Background: Tobacco and alcohol consumption are considered as major public health problems in the world. The strenuous nature of the job, long and irregular working hours, long stay in the sea while fishing may lead to an increased rate of tobacco and alcohol consumption in fishermen. Aim of the study was to find out the prevalence of harmful lifestyle practices among fishermen, and also to find the association between harmful lifestyle practices and selected variables among the fishermen. Methods: A descriptive cross-sectional study was carried out among 275 fishermen in Cuddalore district, Tamil Nadu during October 2021 to March 2022. A Pre tested, semi-structured proforma was used to collect data about the basic socio-demographic variables, detailed occupational history, health status of fishermen and tobacco consumption and alcohol intake. Data were entered in Microsoft excel and analysis was done using statistical package for social sciences (SPSS) version 17. Results: The proportion of cigarette smoking, tobacco chewing and alcohol consumption was 24.7%, 15.3% and 19.6% respectively. Variables such as boat ownership, diabetes, hypertension, sleep duration, income were found to be statistically significant. Conclusions: Harmful lifestyle practices among fishermen found